Measurement of biliary alkaline phosphatase by mini-column chromatography and by electrophoresis and its application to the detection of liver metastases in patients with breast cancer. Issue 2 (February 1984) - Karmen, C; Mayne, P D; Foo, A Y; Parbhoo, S; Rosalki, S B
Abstract : We describe a simple, rapid, and reproducible ion exchange mini-column chromatographic method for the quantitative measurement of biliary alkaline phosphatase in plasma. We have used this method to evaluate a cellulose acetate electrophoretic method, which was used to assess the value of measuring biliary alkaline phosphatase in 85 patients with breast cancer investigated for possible hepatic metastases. Biliary alkaline phosphatase activity was abnormal in 19 of 24 patients (79%) with liver metastases, but abnormalities were also found in 12 of 61 patients (20%) without hepatic metastases; in only 37% of patients with positive test results was this a consequence of liver metastases. For the identification of liver metastases, therefore, the method has useful sensitivity but limited specificity. Neither sensitivity nor specificity was significantly better than that of plasma gamma-glutamyltransferase activity, which was measured concomitantly.